Solvent Vapor Annealing Upgraded Orderly Intermolecular Stacking and Crystallinity to Enhance Memory Device Performance. Issue 16 (13th July 2020) - Guo, Chunxiu; Zhang, Qijian; Li, Hua; Lu, Jianmei
Abstract: Molecular stacking and crystallinity in a film can effectively affect the charge‐carrier mobility of semiconductor materials and corresponding device performance. Currently, solvent vapor annealing (SVA), as an effective thin‐film optimization strategy, which can select the appropriate solvent according to the characteristics of the molecular structure to optimize the intermolecular orderly arrangement, is often adopted. Thus, a small conjugated molecule C20 ‐ID(TPCN)2 with flexible alkyl side chains was synthesized and applied as active layer of sandwich memory devices. The active layer film has been annealed with different polar solvent vapors to evaluate the relationship among the molecular structure, solvent selection, annealing parameters and intermolecular stacking. Compared to un‐annealed devices, the memory devices based on the films through CH2 Cl2 ‐annealing show better performance with a lower threshold voltage due to developed ordered molecular aggregation and better crystallinity, while a hydrophilic solvent vapor will weaken the device performance. This work not only reveals that selecting an appropriate solvent vapor for the molecular structure could be of vital importance in inducing the desired intermolecular stacking mode, but also provides a novel insight for the realization of organic semiconductor devices with excellent performance. Abstract : By treating the deposition films of small‐molecule C20 ‐ID(TPCN)2 with different polar solvents vapor annealing, the effect of the solvent selection, molecular structure as well as annealing parameters on the controllable stacking of directionally induced molecules was investigated.